2006
DOI: 10.1542/peds.2006-2481
|View full text |Cite
|
Sign up to set email alerts
|

Menstruation in Girls and Adolescents: Using the Menstrual Cycle as a Vital Sign

Abstract: Young patients and their parents often are unsure about what represents normal menstrual patterns, and clinicians also may be unsure about normal ranges for menstrual cycle length and amount and duration of flow through adolescence. It is important to be able to educate young patients and their parents regarding what to expect of a first period and about the range for normal cycle length of subsequent menses. It is equally important for clinicians to have an understanding of bleeding patterns in girls and adol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
121
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 450 publications
(126 citation statements)
references
References 29 publications
3
121
0
2
Order By: Relevance
“…Additionally, body composition was assessed using a Bodystat 1500 analyzer (Douglas, Isle of Man). Standard physical examination included the assessment of the hirsutism score on the Ferriman-Gallwey scale of ≥8 points [17]. Severity of acne using 10 points on the visual analogue scale (≥6 points was considered as severe), seborrhea and alopecia (the clinical markers of hyperandrogenism) were also assessed.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, body composition was assessed using a Bodystat 1500 analyzer (Douglas, Isle of Man). Standard physical examination included the assessment of the hirsutism score on the Ferriman-Gallwey scale of ≥8 points [17]. Severity of acne using 10 points on the visual analogue scale (≥6 points was considered as severe), seborrhea and alopecia (the clinical markers of hyperandrogenism) were also assessed.…”
Section: Methodsmentioning
confidence: 99%
“…In women with adenomyosis and without, exactly half of them were in the secretory phase. Their amount of menses during menstruation was grouped into three classes: light, moderate, and heavy, depending on whether they changed their sanitary pads <3, between 3 and 6, or >6 times a day, respectively [23]. The severity of dysmenorrhea was classified according to the Verbal Descriptor Scale as mild, moderate, and severe, as reported previously [21,24].…”
Section: Methodsmentioning
confidence: 99%
“…The majority of our adolescents reported regular menses for their gynecological age [23]. The 2 girls with menstrual irregularities presented disorders affecting menstrual cycle as mild hyperprolactinemia or polycystic ovary syndrome [24]. In the latter, the family history demonstrated that the mother and the aunt were also affected by the same disorder, suggesting a familial inheritance.…”
Section: Discussionmentioning
confidence: 99%
“…In the latter, the family history demonstrated that the mother and the aunt were also affected by the same disorder, suggesting a familial inheritance. In this patient, CPP likely represented an early manifestation of polycystic ovary syndrome [24], and oligomenorrhea was not related to the previous GnRH analogue therapy. Transient mild increase of prolactin has been reported in girls who underwent triptorelin depot administration for CPP; however, the hormone values normalized within 6–12 months after the discontinuation of the GnRH analogue [25].…”
Section: Discussionmentioning
confidence: 99%